(untitled) (Journal of Pharmaceutical Negative Results, 2023)
Wound healing is a challenging clinical problem which needs efficient wound management. Wound is a disruption of the typical anatomical structure and function of skin which can also leads to the organ damage. The wound healing can be divided into 4 major phases according to their mechanism of action i.e Hemostasis, Inflammation, Proliferation and Remodeling. Various allopathic formulations are available for wound healing but with possible drawbacks, So,now a days herbal plants are gaining much popularity for treatment of various ailments. This research article focused on the role of herbal plants in wound healing which was accompanied by formulating and evaluating the wound healing assessment by using incision wound model. In this research article polyherbal ointment was prepared using honey, Ocimum sanctum extract,Aloe vera gel extract and Lemon peel extract. The formulation was evaluated for various parameters and finally subjected to animal study for assessing its wound healing property. Formulation F-C (7%w/w) showed significant(P<0.001) result when compared with negative control. Marketed formulation was also showed significant result.